Penerapan Model Discovery Learning Berbantuan Video Animasi Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Turunan Fungsi Aljabar Kelas XI IPA Madrasah Aliyah Al-Hikmah Soe - Lewa, Mawardah S.; Ekowati, Ch. Krisnandari; Nada, Yohanes H. (Pendidikan Matematika FKIP Universitas Mataram, 2024)
This research was motivated by the low learning outcomes of class XI Science at Madrasah Aliyah Al-Hikmah Soe on algebraic function derivatives. The aim of this research is to describe the application of the discovery learning model assisted by animated videos to improve the learning outcomes of class The research method used is Classroom Action Research (PTK), with qualitative and quantitative data types. Data collection techniques in this research were through observation, tests and questionnaires, with the instruments used namely teacher and student observation sheets, test questions and student response questionnaires. Implementation of this Classroom Action Research has 4 stages, namely 1) Planning; 2) Implementation of action (action); 3) Observation; 4) Reflection. The research results showed that the percentage of completeness of students' classical learning outcomes at the end of cycle I reached 50%, increasing to 90% at the end of cycle II and was in very good criteria. The implementation of teacher teaching activity score data at the end of cycle I reached 95.18%, increasing to 96.93% at the end of cycle II and was in very good criteria. In addition, the implementation of student learning activity score data at the end of cycle I reached 91.25% and also increased to 95% at the end of cycle II and was in the very good criteria.